Handbook of Plant Ecophysiology Techniques - Reigosa Roger, Manuel J; Ed (SPRINGER, 2001)
"This book is intended to be useful for people interested in Plant Ecophysiology research or related sciences. It will also be useful for scientists working in Forestry or Agronomy." "Twenty-seven chapters cover a wide variety of techniques, ranging from electron microscopy applied to seed germination, flow cytometry applied to different measures, cell cycles studies, field and lab measures related to photosynthesis (from pigments to gas exchange and fluorescence), determination of water related parameters, and techniques to measure phenolics, total soluble proteins, stress, proteins, polyamines, proline, RubisCO activity, ATPases, ABA and ions interchange." "Every chapter includes both physiological aspects of the measured parameter and the chosen reference technique for that parameter. A special emphasis is put on the allelopathy research, although the book will be valuable for the study of any kind of stress. All chapters can be read independently, and both expert and unexperienced scientists will benefit from the handbook."--BOOK JACKET.